Comparative Evaluation of Leukocyte Platelet-Rich Plasma and Platelet-Rich Plasma on the rate of Orthodontic Tooth Movement: A Split Mouth Study - Peddi, Sunayana; Manne, Ranjit Kumar; Gandikota, Chandrasekhar (Orthodontic Journal of Nepal, 2024)
Introduction: One of the most common concerns among orthodontic patients is the duration of treatment for which the rate of orthodontic tooth movement must be accelerated. Corticotomy, piezocision, micro-osteoperforation and platelet-rich plasma injection are a few examples to accelerate tooth movement. Limited data is available on the use of leukocyte platelet-rich plasma to accelerate orthodontic tooth movement in humans. Therefore, this study aimed to evaluate and compare the effects of platelet-rich plasma and leukocyte platelet-rich plasma on the rate of orthodontic tooth movement. Materials and Method: This study included 12 adult patients undergoing orthodontic treatment requiring extraction of all four fist premolars. It used a split mouth design where one side of the oral cavity was injected with platelet-rich plasma and the other side was injected with leukocyte platelet-rich plasma in both the arches, distal to the canine. The injections were given at the end of every 4 weeks for 3 months consecutively and the amount of space closure was measured every 4 weeks using digital vernier calipers. Result: The results showed that the rate of tooth movement was accelerated between different time intervals when platelet-rich plasma and leukocyte platelet-rich plasma were injected. However, the comparison between platelet-rich plasma and leukocyte platelet-rich plasma did not show statistical significance in upper and lower arches. Conclusion: Platelet-rich plasma and leukocyte platelet-rich plasma increase the rate of tooth movement and reduce the treatment duration overall. However, when platelet-rich plasma and leukocyte platelet-rich plasma were compared, the rate of acceleration by both products was nearly identical.